The Relationship between Academic Discipline and Dialogic Behavior in Open University Course Forums - Gorsky, Paul; Caspi, Avner; Antonovsky, Avishai; Blau, Ina; Mansur, Asmahan (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2010)
The objective of this study was to determine the relationship between disciplinary difference (exact and natural sciences versus humanities) and the dialogic behavior that occurred in Open University course forums. Dialogic behavior was measured in terms of students’ and instructors’ active participation in the forum (posting a message) as well as amounts and proportions of “teaching presence,” “cognitive presence,” and “social presence.” We found that active participation in the science forums was much higher than in the humanities forums. We also found a ratio among the three presences that was constant across different academic disciplines, as well as across different group sizes and course types.